2019
DOI: 10.1111/tbed.13008
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective detection and phylogenetic analysis of swine acute diarrhoea syndrome coronavirus in pigs in southern China

Abstract: Swine acute diarrhea syndrome coronavirus (SADS-CoV), a novel coronavirus, was first discovered in southern China in January 2017 and caused a large scale outbreak of fatal diarrheal disease in piglets. Here, we conducted a retrospective investigation of 236 samples from 45 swine farms with a clinical history of diarrheal disease to evaluate the emergence and the distribution of SADS-CoV in pigs in China. Our results suggest that SADS-CoV has emerged in China at least since August 2016. Meanwhile, we detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 22 publications
3
55
0
Order By: Relevance
“…4, five strains (SD01 , SD03-2018, SD05-2018, SD06-2018and SD08-2018 W. Sun, et al Virus Research 278 (2020) 197869 Swine acute diarrhea syndrome coronavirus (SADS-CoV), also named as Swine enteric alphacoronavirus (SeACoV) (Fu et al, 2018;Zhou et al, 2018) and PDCoV. Outbreaks of these enteric coronaviruses have been reported in China, causing substantial economic losses in the swine industry (Qing et al, 2016;Zeng et al, 2015;Zhou et al, 2019). In 2014, PDCoV was first detected in China, causing tremendous financial losses in the swine industry, and the virus has rapidly spread nationwide Liu et al, 2018;Mai et al, 2018a;Song et al, 2015;Wang et al, 2018b).…”
Section: Novel Amino Acid Deletions or Insertions Were Detected In Thmentioning
confidence: 99%
“…4, five strains (SD01 , SD03-2018, SD05-2018, SD06-2018and SD08-2018 W. Sun, et al Virus Research 278 (2020) 197869 Swine acute diarrhea syndrome coronavirus (SADS-CoV), also named as Swine enteric alphacoronavirus (SeACoV) (Fu et al, 2018;Zhou et al, 2018) and PDCoV. Outbreaks of these enteric coronaviruses have been reported in China, causing substantial economic losses in the swine industry (Qing et al, 2016;Zeng et al, 2015;Zhou et al, 2019). In 2014, PDCoV was first detected in China, causing tremendous financial losses in the swine industry, and the virus has rapidly spread nationwide Liu et al, 2018;Mai et al, 2018a;Song et al, 2015;Wang et al, 2018b).…”
Section: Novel Amino Acid Deletions or Insertions Were Detected In Thmentioning
confidence: 99%
“…These large, industrial swine farms, commonly known as confined animal feeding operations (CAFOs), are thought to be sites for novel pathogen emergence and transmission. In recent years, swine pathogen epizootics in China have included porcine reproductive and respiratory syndrome virus [4], porcine epidemic diarrhea virus [5], swine acute diarrhea syndrome coronavirus [6], and, most recently, a 2018-19 massive outbreak of African Swine Fever [2].…”
mentioning
confidence: 99%
“…The phylogenetic analysis based on the whole genome and N gene of eight SADS-CoVs and other CoVs showed that all the sequences of SADS-CoVs clustered with bat coronavirus HKU2 to form a well-defined branch and belong to the α-genera [25]. However, surprisingly/interestingly, the phylogenetic analysis of the S genes showed that the S gene cluster can be divided into two groups: α-CoV-1 and α-CoV-2.…”
Section: Resultsmentioning
confidence: 99%